The Protective Effect of Garlic Extract againstAcetaminophen-Induced Loss of Mitochondrial MembranePotential in Freshly Isolated Rat Hepatocytes: Effect of garlic extract against acetaminophen cytotoxicity - Mahdieh Anoush; Mohammad Ali Eghbal; Hossein Hamzeiy; Fatemeh Fathiazad; Nazli Saeedi Kouzehkonani (Iranian Journal of Pharmaceutical Sciences, 2009)
Overdose of acetaminophen causes severe hepatic necrosis in humans and experimental animals. Studies on its hepatotoxicity remain a very active area since some of current data are still uncertain. In this study, freshly isolated rat hepatocytes were used to determine the effects of garlic extract and its component, allicin on the acetaminophen-induced cell cytotoxicity and to compare with the effect of N-acetyl cysteine as a standard treatment. Garlic extract was prepared via a standardmethod and its allicin and allyl mercaptan contents were determined using analytical and preparative high performance liquid chromatography (HPLC). Rat hepatocytes were isolated using collagenase perfusion and mitochondrial membrane potential and cell cytotoxicity were determined using Rhodamine 123 fluorescence and trypan blue exclusion, respectively. Inclusion of garlic extract and/or N-acetyl cysteine resulted in a reduction in the loss of mitochondrial membrane potential as well as cell death which occurred after acetaminophen addition and therefore,illustrated considerable hepatoprotective effects without significant differences between two treatments. In contrast, pure allicin was not effective significantly. The hepatoprotective effects of garlic extract may be due to the compounds other than allicin such as allyl mercaptan, as allicin has been shown to transform to allyl mercaptan as a major metabolite.